GE_GERICHTE P/8841/2013 vom 13. Mai 2014 - GE Cour de justice (2014)
INFRACTIONS CONTRE L'HONNEUR ; INJURE ; PLAINTE PÉNALE ; DÉLAI ; RETARD ; FRAIS DE LA PROCÉDURE ; LIEN DE CAUSALITÉ | CPP.310; CP.173; CP.174; CP.177; CP.31; CPP.427